Exploring Job Interview Skills of Future Engineers: Application of Appraisal Analysis Assessment and Verbal Impression Management - Mohd Noor, Siti Noor Fazelah; Md Tab, Fazita; Kamarulzaman, & Robijah (Journal of Technical Education and Training, 2017)
The issue of employability among engineering graduates has been examined, debated and tried to be resolved by various organizations and researchers. The lack of employability skills especially communication skills causes graduates struggling to fulfill current work demands and professional expectations in order to succeed in today’s fast-changing and global working environments. Communication skills are a crucial factor of employability, thus there is a need for quality assessment especially in job interview to enhance communicative competence of undergraduates. This research aims to unfold and assess what and how job candidates perform in a mock job interview and how they are being judged by the interviewers. It also studies the underlying linguistic evidence in job interviews of future engineers under the conditions of English as a Second Language (ESL) by applying Appraisal analysis (Attitude subsystems) of Systemic Functional Linguistics and Verbal Impression Management. The findings revealed that future graduates who possess certain elements of linguistics competencies are better in answering and some are in dire need to be equipped with the skills of job interview in preparing them to be employable. It can be concluded that good communication skills especially the job interview skills as what the industry required and persisted are not only based on the fluency of English but the ability to present ideas explicitly and facts using appropriate words and positiveness. The study also recommends the need to assess the future engineering graduates’ linguistics abilities in preparing them to be employable.